PROCEDURAL STATUS OF A VICTIM OF DOMESTIC VIOLENCE IN CRIMINAL PROCEEDINGS - Adamenko, Oleg (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
The purpose of the article is to study the procedural status of a victim of domestic violence in criminal proceedings, to highlight and substantiate proposals aimed at improving domestic criminal legislation. Research methods: a comprehensive analysis of normative legal acts, scientific literature and the practice of applying criminal procedural legislation was used. Results: the procedural status of a victim of domestic violence is defined as a set of rights and obligations that arise for a person who has suffered psychological, physical, sexual and/or property damage as a result of a criminal offense. It was established that, taking into account the prospects for the development of criminal justice and the experience of other states in this direction, it can be confidently stated that the category of a victim of domestic violence and its procedural status has not yet been fully formed, it needs significant improvements, changes and additions, because significant gaps in the current legislation significantly complicate criminal proceedings in cases of domestic violence. It is noted that in the framework of criminal proceedings, the completeness of the legal regulation of procedural relations depends on their clear regulation in criminal legislation, with the establishment of not only the rights, freedoms, legal interests and obligations of these participants, but also the regulated algorithm of actions of all participants in the relevant proceedings. Discussion: the norms of domestic legislation that regulate the issue of the procedural status of a victim of domestic violence in criminal proceedings have a fragmentary nature in a number of domestic legal acts that do not cooperate with each other, and therefore require clarification and improvement.